Role of moral foundations in the nuclear disarmament of South Africa - Das, Arunjana (Scientia Militaria - South African Journal of Military Studies, 2022)
South Africa is the only country in the world that successfully acquired a nuclear deterrent capability in the form of six nuclear devices and dismantled them completely. Extant explanations include strategic reasons, i.e.., its security conditions changed subsequent to the removal of the Soviet threat after the Soviet collapse in 1989 and an end of superpower rivalry in Africa; South Africa’s increasing isolation on account of apartheid; pressure from the US, and concerns about undeclared nuclear technology falling in the hands of a Black-led government. Whereas these factors potentially contributed to the eventual dismantlement, the world-wide campaign led by domestic and transnational movements that sought to make moral claims by connecting the cause of anti-apartheid to that of anti-nuclear likely played a role. I apply Moral Foundations Theory (MFT) to the South Africa case to explore the role played by moral claims in the eventual disarmament.